Mga kuwentong-bayan ng katimugang Pilipinas - Casanova, Arthur P. (Arthur de la Pena); Esteban, Rolando C. 1959-; Esteban, Ivie C. (Anvil Publishing, Inc., 2011)
Collection of folktales from Mindanao.